THE USE OF TED TALK AND GRAMMARLY TO IMPROVE STUDENTS’ SPEAKING AND WRITING ABILITY AT SMK YAPIM PEKANBARU - Kumalasari, Cyintia; Marhamah, Marhamah (Universitas Muhammadiyah Makassar, 2024)
Writing in English is still challenging and requires a strong ability in grammar. Besides, communicating ideas through the English language is still difficult for some students. This study aims to analyse the students’ perceptions through the use of the Grammarly application to help with writing skills and the TED Talk application to help improve speaking skills. The use of these applications is to help students in English skills that have grown these recent days, as well as the development of technology. Research participants include 15 students of SMKS Yapim Pekanbaru, department of Network and Computer Engineering. The research methods for the study included a questionnaire, as well as in-depth interviews that were conducted to explore the students’ perception of using TED Talk and Grammarly applications. Both applications will make students more involved in learning English, especially speaking and writing. Because of its practicality dan ease of access, the students are not difficult to use. The conclusion is that there have been some students who can write their ideas with the help of the Grammarly application and also watch TED Talk, then present them in front of the class.